Numerical investigation and cost analysis of FRP-concrete unidirectional hybrid slabs - Mahboob, Amir; Eskenati, Amir Reza; Moradalizadeh, Soheil (Zielona Góra: Uniwersytet Zielonogórski)
Fiber-reinforced polymer (FRP) has been commonly used to reinforce concrete structures. The kinds of FRP demonstrate an effective alternative to various methods of reinforcement in concrete structures subjected to bad environmental conditions which cause corrosion and damage to concrete.
Keywords: CFRP; GFRP; AFRP; hybrid slabs; numerical simulation; costs